Interperiod coherent integration of the received signal with a variable repetition period of the probing signal - S. R. Heister; P. G. Semashko (Doklady Belorusskogo gosudarstvennogo universiteta informatiki i radioèlektroniki, 2021)
Interperiod coherent integration of the received signal provides an increase in the signal-to-noise ratio and is simply implemented with a fixed repetition period of the probing signals. In practice, pulsed radars use a variable repetition period to protect against blind speeds. The algorithms of the interperiod coherent integration with a variable repetition period have been developed and their features have been revealed, which are advisable to take into account in the practical implementation in the radars. These features determine the complexity of the interperiod coherent integration algorithm, the radial velocity (Doppler frequency) survey interval and the spectrum features. An algorithm is developed with simultaneous interperiod coherent integration of the received signal and a single-delay clutter cancelation in the spectral domain in the case of variable repetition period of the probing signals. The quantitative indicators obtained by modeling are presented and a comparative analysis is carried out.